Visualizing BDNF Transcript Usage During Sound-Induced Memory Linked Plasticity - Matt, Lucas; Eckert, Philipp; Panford-Walsh, Rama; Geisler, Hyun-Soon; Bausch, Anne E.; Manthey, Marie; Müller, Nicolas I. C.; Harasztosi, Csaba; Rohbock, Karin; Ruth, Peter; Friauf, Eckhard; Ott, Thomas; et al. (Frontiers in Molecular Neuroscience, 2018)
Activity-dependent BDNF (brain-derived neurotrophic factor) expression is hypothesized to be a cue for the context-specificity of memory formation. So far, activity-dependent BDNF cannot be explicitly monitored independently of basal BDNF levels. We used the BLEV (BDNF-live-exon-visualization) reporter mouse to specifically detect activity-dependent usage of Bdnf exon-IV and -VI promoters through bi-cistronic co-expression of CFP and YFP, respectively. Enriching acoustic stimuli led to improved peripheral and central auditory brainstem responses, increased Schaffer collateral LTP, and enhanced performance in the Morris water maze. Within the brainstem neuronal activity was increased and accompanied by a trend for higher expression levels of Bdnf exon-IV-CFP and exon-VI-YFP transcripts. In the hippocampus BDNF transcripts were clearly increased parallel to changes in parvalbumin expression, and were localized to specific neurons and capillaries. Severe acoustic trauma, in contrast, elevated neither Bdnf transcript levels, nor auditory responses, parvalbumin or LTP. Together, this suggests that critical sensory input is essential for recruitment of activity-dependent auditory-specific BDNF expression that may shape network adaptation.